Women at Work: How Organization Manage Career Women Performance at Manufacturing in Jababeka – Bekasi - Grace Amin; Cici Lestari Agustina (Jurnal Manajemen, 2020)
This research analyzed career women performance at manufacturing industries. Researchers used quantitative and qualitative methods. There were 200 career women in manufacturing industries around Bekasi joined as respondents in this research and filled the questionnaire given. Data was analyzed by multiple linear regression. Researchers also interviewed representative respondents in order to get respondent perspective about work life balance, family conflict and quality of work life. This research found that work life balance, family conflict, and quality of work life have significant influence towards career women performance on manufacturing industries around Bekasi.